2008
DOI: 10.1063/1.2903147
|View full text |Cite
|
Sign up to set email alerts
|

Real-time evolution of tunneling magnetoresistance during annealing in CoFeB∕MgO∕CoFeB magnetic tunnel junctions

Abstract: Articles you may be interested inEffects of boron composition on tunneling magnetoresistance ratio and microstructure of CoFeB/MgO/CoFeB pseudo-spin-valve magnetic tunnel junctions

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 28 publications
2
22
1
Order By: Relevance
“…A rapid increase of the TMR ratio is seen at the beginning, in particular for annealing temperatures of 300 • C and above, followed by a slower increase. The same behavior has been reported by Wang et al before [17]. In a subsequent paper [18], these authors studied the kinetics of crystallization processes by x-ray diffraction and electron microscopy and identified the crystallization of CoFeB in an inhomogeneous solid-state epitaxy mode.…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…A rapid increase of the TMR ratio is seen at the beginning, in particular for annealing temperatures of 300 • C and above, followed by a slower increase. The same behavior has been reported by Wang et al before [17]. In a subsequent paper [18], these authors studied the kinetics of crystallization processes by x-ray diffraction and electron microscopy and identified the crystallization of CoFeB in an inhomogeneous solid-state epitaxy mode.…”
Section: Resultssupporting
confidence: 58%
“…The kinetics of the processes occurring during annealing have been studied in detail [17][18][19]. Specific useful information has been obtained from the time evolution of the TMR ratio during annealing.…”
Section: Introductionmentioning
confidence: 99%
“…14 High TMR ratio over 400% was observed for MTJs with x = 20% and 40%. It has been suggested that the high TMR ratios at T a above 475°C are related to the improved quality of MgO barrier, 17,18 in addition to the crystallization of initially amorphous CoFeB to highly oriented bcc ͑001͒ textured CoFeB. 4,19,20 Note that CoFeB electrodes start to form bcc ͑001͒ textures at a much lower annealing temperature of T a = 325°C ͑Refs.…”
mentioning
confidence: 97%
“…This work confirms a crystalline albeit textured and columnar growth after annealing of both MgO and CoFe, layers. Wang et al 11 confirmed by x-ray scattering an improved crystallinity of the MgO͑001͒ layer as the reason for the increasing TMR value measured at high annealing temperatures. At 380°C, the MgO͑002͒ Bragg reflection intensity increases with annealing time and the full width at half maximum ͑FWHM͒ decreases.…”
Section: Introductionmentioning
confidence: 70%